ACCOUNTING-INFORMATION SUPPORT MANAGEMENT OF WOODWORKING ENTERPRISES FOR THE PRODUCTION OF SOLID BIOFUELS - Pylypiv, N.I.; Piatnychuk , I. D.; Markiv M.М. (The actual problems of regional economy development, 2016)
In the article the issue of formation of the basic principles of accounting and information support of wood-processing enterprises for the production of solid biofuels for their sustainable development and competitiveness, defined requirements management, provided the relationship between the stages of your process and information flows in terms of resource and enerhozberezhennya.U The study found that for a more complete and efficient accounting and information support of enterprises required building management accounting by implementing these steps in your process as technology together: preliminary (preparatory), primary, current, analytical and outcome to ensure implementation of management objectives for reliable information as retrospective and prospective nature of the efficient use of resources in manufacturing products. JEL: M41